Discovery of the first A1 adenosine receptor ligand based on the chromone scaffold. Issue 52 (12th May 2016) - Cagide, F.; Reis, J.; Gaspar, A.; Chavarria, D.; Kachler, S.; Klotz, K. N.; Gomes, L. R.; Low, J. N.; Vilar, S.; Hripcsak, G.; Borges, F.
Abstract : The first potent and selective hA1 AR ligand based on the chromone scaffold is reported in this work. Abstract : The first potent and selective hA1 AR ligand based on the chromone scaffold is reported in this work. Receptor-driven molecular modeling studies provide valuable information about the molecular interactions responsible for the high affinity of N -(2-nitrophenyl)-4-oxo-4 H -chromene-2-carboxamide to the hA1 AR ( K i = 0.219 μM) and reinforce the crucial role of AR affinity of the amide linker located at C-2 of the pyrone ring.